2014
DOI: 10.2527/jas.2013-6851
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing metabolizable protein to ewes during late gestation: I. Effects on ewe performance and offspring performance from birth to weaning1

Abstract: We hypothesized that a maternal diet greater in MP during the last third of gestation would yield improved offspring growth due to enhanced placental or mammary gland function. Our objective was to determine how MP intake during late gestation affected ewe and offspring performance from birth to weaning in ewes fed diets similar in total energy. In yr 1, maternal dietary treatments were applied at d 100 of gestation, were similar in total energy, and contained 60% of MP requirements (60MP1), 80% of MP requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
2
14
3
Order By: Relevance
“…This is possible because a maternal diet greater in metabolizable protein during the last third of gestation would improve offspring growth due to enhanced placental or mammary gland function (Paim et al, 2013;Van Emon et al, 2014). Thus, the objective of this study was to evaluate the effect of concentrate supplementation in last third of gestation and during lactation on the weight gain of F1 Dorper × Morada Nova lambs and F1 Dorper × Santa Inês lambs reared in a creep-feeding system.…”
Section: Introductionmentioning
confidence: 99%
“…This is possible because a maternal diet greater in metabolizable protein during the last third of gestation would improve offspring growth due to enhanced placental or mammary gland function (Paim et al, 2013;Van Emon et al, 2014). Thus, the objective of this study was to evaluate the effect of concentrate supplementation in last third of gestation and during lactation on the weight gain of F1 Dorper × Morada Nova lambs and F1 Dorper × Santa Inês lambs reared in a creep-feeding system.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we concluded that increased maternal MP intake may positively impact the ewe, without altering offspring performance from birth to weaning [7]. Our hypothesis was that isocaloric diets deficient in MP would not hinder conceptus or mammary development as weaning weights were not affected in a sister study [7].…”
Section: Introductionmentioning
confidence: 83%
“…Ewes were acclimated to low-quality hay (Table 1) and a supplement which met 100% of MP requirements (MP100), as determined by National Research Council (2007), for 10 d before starting dietary treatment [7]. The low-quality hay was used to limit MP intake.…”
Section: Animals and Dietsmentioning
confidence: 99%
See 2 more Smart Citations